Bloodless Operations in the Surgical Treatment of Mitral-Aortic Heart Disease in Conditions of Artificial Circulation - Gumeniuk, B. M.; Popov, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Traditional mitral and aortic valve replacement in conditions of artificial blood circulation (ABC) involves the use of blood products. Given various complications arising in perioperative period, the authors propose a technique for “bloodless operations” without the use of donor blood, without the use of columns, and the “sell-saver” method. From January 1, 2011 to December 31, 2018, mitral-aortic valve replacement was performed in 79 patients; in 42 of them blood products were used during surgery, and in 37 patients donor blood components were not used. The method of anaesthetic and infusion-perfusion measures for mitral-aortic valve replacement in conditions of ABC is given. The use of the blood-saving method has allowed to obtain good clinical effect without transfusion complications in perioperative period, which facilitated the use of bloodless methods for mitral-aortic valve replacement in the main group in conditions of ABC and reduce blood transfusions in perioperative period from 27.4 % to 10.3 % of the circulating blood volume (CBV), compared to the control group. In the variant of reservation of autoblood “A+B+C” and exfusion of 27.2% of the CBV, the most effective variants of the blood-saving) technology were observed during mitral-aortic valve repair in conditions of ABC.